2022
DOI: 10.1155/2022/6065494
|View full text |Cite
|
Sign up to set email alerts
|

Phillyrin Prevents Ovariectomy-Induced Osteolysis by Inhibiting Osteoclast Differentiation

Abstract: Postmenopausal osteoporosis is a metabolic disease caused by an imbalance between osteoclasts and osteoblasts. At present, the drug strategy for treating postmenopausal osteoporosis has some limitations and is unable to satisfy the demands of patients. Phillyrin (Phil) is an herbal extract from Forsythiae Fructus, with an inhibitory effect on osteolysis. In this study, we described the role of Phil in ovariectomy-induced osteoporosis and its effect on osteoclast differentiation in vitro. Eighteen female C57BL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Recent studies reported on the anti-inflammatory effect of OFL containing a phenylpropyl triterpenoids and phillyrin in the macrophages treated with lipopolysaccharide [ 9 , 11 ]. Furthermore, Zhang et al, reported that the phillyrin prevented osteolysis via the inhibition of osteoclast differentiation [ 12 ]. Hence, we hypothesized that the OFL, with its anti-inflammatory effects, might suppress or delay the osteoclastic bone loss through the downregulation of pro-inflammatory factors associated with the osteoclastogenesis of macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported on the anti-inflammatory effect of OFL containing a phenylpropyl triterpenoids and phillyrin in the macrophages treated with lipopolysaccharide [ 9 , 11 ]. Furthermore, Zhang et al, reported that the phillyrin prevented osteolysis via the inhibition of osteoclast differentiation [ 12 ]. Hence, we hypothesized that the OFL, with its anti-inflammatory effects, might suppress or delay the osteoclastic bone loss through the downregulation of pro-inflammatory factors associated with the osteoclastogenesis of macrophages.…”
Section: Introductionmentioning
confidence: 99%